ELIMINATION OF DUPLICATE PACKETS FROM THE NETWORK USING REDUNDANCY AWARE HIERARCHICAL TREE ALTERNATIVE PATH ALGORITHM - Thayyil, Chinnu.J.; Glory, P.J.Gladys (IJRDO -Journal of Computer Science Engineering, 2016)
The wireless sensor network (WSN)is a grouping of sensing, computation, andcommunication into a particular tiny device.A sensor network consists of an array ofmany sensor networks of various typesunified by a wireless communicationnetwork. This paper has largely describedthe feature and the substance of congestioncontrol in WSN and survey the study relatedto the Congestion Control Protocols andAlgorithms for WSNs. In this paper weapplied Redundancy Aware HierarchicalTree Alternative Path (RAHTAP) algorithm,this algorithm eliminates the duplicatepackets from the network and attainreduction in network load as per packetsbasis which generate lively substitute pathfrom source to sink.